Measles vaccine effectiveness and risk factors for measles in Dhaka, Bangladesh - Akramuzzaman Syed M.; Cutts Felicity T.; Hossain Md J.; Wahedi Obaidullah K.; Nahar Nazmun; Islam Darul; Shaha Narayan C.; Mahalanabis Dilip (The World Health Organization, 2002)
OBJECTIVE: To evaluate vaccine effectiveness and to assess risk factors for measles in Dhaka, Bangladesh. METHOD: A case-control study, involving 198 cases with 783 age-matched neighbourhood controls and 120 measles cases with 365 age-matched hospital controls, was conducted in 1995-96 in three large hospitals in Dhaka. FINDINGS: Measles vaccine effectiveness was estimated at 80% (95% confidence interval (CI) = 60-90%) using neighbourhood controls; very similar results were obtained using hospital controls. Visits to a health facility 7-21 days before onset of any symptoms were associated with increased risk of measles compared with neighbourhood (adjusted odds ratio (OR) = 7.0, 95% CI = 4.2-11.6) or hospital (adjusted OR = 1.7, 95% CI = 1.01-2.8) controls. Cases were more likely than controls to come from a household where more than one child lived (adjusted OR = 1.6, 95% CI = 1.1-2.5 versus neighbourhood controls; adjusted OR = 1.8, 95% CI = 1.02-3.0 versus hospital controls). CONCLUSIONS: To improve measles control in urban Dhaka missed immunization opportunities must be reduced in all health care facilities by following WHO guidelines. For measles elimination, more than one dose of vaccine would be required.